The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1111/jop.12353
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of Ashwagandha against human head and neck cancer cell lines

Abstract: These suggest that MEAG and WA may be potential natural materials for the treatment of HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…22,23 Our research group also reported that the methanol extract of Smilax china L. or b-phenylethyl isothiocyanate induced the DR5/caspase-8/Bid axis by regulating the extracellular signal-regulated kinase (ERK) or p38 MAPK signaling pathway, leading to caspase-mediated apoptosis in oral or cervical cancer cells. [24][25][26][27] These previous findings fully support DR5 regulation by natural products during apoptotic cell death pathways in cancer. In this study, our human apoptosis antibody array data showing that silymarin upregulates DR5 protein are consistent with these findings.…”
Section: Discussionsupporting
confidence: 73%
“…22,23 Our research group also reported that the methanol extract of Smilax china L. or b-phenylethyl isothiocyanate induced the DR5/caspase-8/Bid axis by regulating the extracellular signal-regulated kinase (ERK) or p38 MAPK signaling pathway, leading to caspase-mediated apoptosis in oral or cervical cancer cells. [24][25][26][27] These previous findings fully support DR5 regulation by natural products during apoptotic cell death pathways in cancer. In this study, our human apoptosis antibody array data showing that silymarin upregulates DR5 protein are consistent with these findings.…”
Section: Discussionsupporting
confidence: 73%
“…It has also been found to selectively induce cell death in multiple types of tumor cells [143,144]. Its anticancer effects are mediated through modulation of a number of pathways, including inhibition of Notch 1 [145], inhibition of STAT3 activation [146–148], downregulation of the MTOR signalling components pS6K and p4E-BP1 [145], downregulation of the prosurvival pathway Akt/NF-kappaB/Bcl-2 [145], induction of c-Jun-NH(2)-kinase-mediated apoptosis [145], induction of apoptosis via upregulation of Bim, t-Bid, caspase-8, and DR5 [149], suppression of constitutive and IL-6-induced phosphorylation of STAT3 (on Tyr705) and consequent down-regulation of the STAT3 regulated genes Bcl-xL, Bcl-2, cyclin D1 and survivin [150], inhibition of heat shock protein 90 [151], downregulation of COX-2 and iNOS by blocking NF-κB activity [121], and down-regulation of TNF-a [152].…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment with N -acetyl cysteine (NAC) or catalase abrogated withaferin-A-induced up-regulation of both CHOP and DR5 [ 68 ]. The induction of apoptosis in human head and neck carcinoma (MC3 and HN22) cells by withaferin-A was accompanied by upregulation of Bim, truncated Bid (t-Bid), cleavage of caspase-8, -3 and poly ADP ribose polymerase (PARP), and the elevated expression of DR5, suggesting an extrinsic pathway of apoptosis induction by this compound [ 67 ]. Mechanistically, the transcriptional activation of DR5 was mediated through withaferin-A-induced phosphorylation of ERK1/2 and ribosomal S6 kinase, and the induction of ETS-like transcription factor 1 (Elk1) and CHOP [ 78 ].…”
Section: Biochemical Basis Of Anticancer Effects Of Withaferin-amentioning
confidence: 99%